Magnetic Resonance Imaging of Nerve Tumors - Behzad, Barzin; Dianat, Saeed (Seminars in Musculoskeletal Radiology, 2022)
Nerve tumors are uncommon soft tissue neoplasms predominantly arising from peripheral nerve sheath and Schwann cells. We review the manifestations of benign peripheral nerve sheath tumors, concentrating on distinguishing imaging features of schwannomas versus neurofibromas with an emphasis on treatment implications. Nevertheless, there is often an overlap between the imaging presentation of these two conditions, making the accurate radiologic diagnosis challenging. Therefore, tissue sampling is often needed for a definitive histologic diagnosis. Treatment planning largely depends on symptoms, location of the lesion, and underlying risk factors. Three major syndromes, neurofibromatosis type 1, type 2, and schwannomatosis, predispose patients to peripheral nerve sheath tumors (PNSTs), with particular concern about the malignant subtype expression. In patients with suspected PNSTs, correlation of imaging findings with clinical findings and genetic tests is helpful for a more accurate diagnosis and disease management. Some imaging features on magnetic resonance imaging and fluorodeoxyglucose-positron emission tomography can be helpful to differentiate malignant from benign subtypes.
Keywords: peripheral nerve sheath tumor; benign; malignant; neurofibromatosis; magnetic resonance imaging